Eyjafjallajökull Volcanic Ash 2010 Effects on GPS Positioning Performance in the Adriatic Sea Region - Maria Mehmood; Sajid Saleem; Renato Filjar (Atmosphere, 2021)
The Eyjafjallajökull volcanic ash crisis in 2010 temporarily suspended European air traffic operations, as the 39-day eruption caused widely dispersed ashes to enter the lower atmosphere. In this paper, we assessed the effects of this event on the ionosphere layer and, consequently, on GPS positioning. We collected and analysed the data from four IGS stations, nearest to the volcano, for the month of April 2010. We recorded Vertical Total Electron Content (VTEC) time series, analysed their dynamics, and compared them with the GPS positioning errors of a commercial-grade, un-aided, single-frequency GPS receiver (simulating the response of a mass-market GPS receiver). The geomagnetic indices during the time period show little geomagnetic disturbance, especially during the volcanic event. Our results show an enhancement in ionosphere error by up to 15% during the volcanic ash event and an enhanced variance in GPS position components errors. This study reveals the potential impact of the charged volcanic ash on single-frequency, unaided GPS positioning accuracy in the Adriatic Sea region and establishes a foundation for studying similar events in future.